Synthesis and in vitro Evaluation of Zinc Ferrite Nanospheres for Sustained Carvedilol Drug Delivery - Sundaram, Vijayalakshmi; Dhandapani, Balaji (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Magnetic nanoparticles has significant applications, in MRI contrast enhancement, tissue regeneration, cancer therapy, controlled drug delivery etc. The nanoparticles can be tailored to possess specific attributes suitable for distinct biological applications, as a potential drug carriers for sustained drug release. Materials and Methods: The present study focused on synthesizing and utilizing magnetic mesoporous Zn-Ferrite Nanospheres (Zn-Fe NSs) as carriers for controlled drug release systems. Zn-ferrite nanospheres were synthesized by encapsulating the drug carvedilol, by facile solvothermal approach. Thermo Gravimetric Analysis (TGA), Fourier Transforms Infrared Spectroscopy (FT-IR), Transmission Electron Microscopy (TEM), Scanning Electron Microscopy (SEM), Atomic Absorption Spectroscopy, and X-ray Diffraction (XRD) techniques were used to characterize the Zn-Ferrite nanospheres. Results: The average particle size of unloaded and drug-loaded Zn-Ferrite nanospheres was 262.8 nm and 247.6 nm, with polydispersity values of 0.19 and 0.2 Respectively. In vitro drug release studies shown 95.47% cumulative drug release from carvedilol-loaded Zn-Fe NSs after 12 hr at a pH of 7.4. The kinetic studies revealed that the Korsmeyer Peppas model provided the best fit, indicating quasi-Fickian diffusion with a release exponent value of 0.15. Conclusion: The investigation of carvedilol-loaded Zn-Fe NSs revealed a sustained drug release pattern, which is considered crucial for the treatment of cardiovascular diseases, hypertension, cardiopulmonary arrest, and hypertension conditions.
Keywords: Drug delivery; Magnetic nanoparticles; Nanocarrier; Sustained drug release